2020
DOI: 10.1620/tjem.251.207
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbance of Evacuees in Minamisanriku Town after Great East Japan Earthquake: Risk Factors and Treatment

Abstract: In 2011, Minamisanriku Town lost all of its medical facilities during the Great East Japan Earthquake. Using 10,459 anonymized disaster medical records of affected people in Minamisanriku Town, we assessed the prevalence and risk factors of sleep disturbance, which is known to exacerbate non-communicable diseases (NCDs) and anxiety disorder. Because sleep disturbance is a part of mental health issues, we divided the patients into two groups: patients (n = 492) with mental health issues other than sleep disturb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…A binary logistic regression analysis showed that marital status, household type, disaster type, time elapsed after a disaster, subjective health status, depression, and PTSD affect the sleep quality of disaster victims. In a previous study, women and older people were reported to be mentally vulnerable to disaster-like situations [25], and Onose et al [43] reported that women were more susceptible to PTSD. In our study, PTSD was a significant variable affecting sleep quality; however, gender was, surprisingly, not a significant variable in the regression analysis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A binary logistic regression analysis showed that marital status, household type, disaster type, time elapsed after a disaster, subjective health status, depression, and PTSD affect the sleep quality of disaster victims. In a previous study, women and older people were reported to be mentally vulnerable to disaster-like situations [25], and Onose et al [43] reported that women were more susceptible to PTSD. In our study, PTSD was a significant variable affecting sleep quality; however, gender was, surprisingly, not a significant variable in the regression analysis.…”
Section: Discussionmentioning
confidence: 97%
“…One of the main factors associated with stress vulnerability is biological sex [44], and stress is associated with the incidence and severity of several psychiatric disorders, including PTSD and depression, that occur more often in women than in men [44]. Therefore, a sex-based approach to sleep disturbance and mental health management to resolve sleep disturbance would be important in reducing the PTSD resulting from disasters [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noncommunicable disease (NCD) (68%) was the most frequent medical needs, followed by, infectious disease (21%), mental health issues (6%), trauma (4%), and mother and child health issues (0.2%). Using the same database, Nakamura et al (2020) revealed that evacuees had high prevalence of sleep disturbance. Aged population and female gender were the risk factors, but sleep disturbance rather affected younger evacuees regardless of gender who does not have NCD but residing in evacuation center, stressing the importance of awareness of sleep disturbance in such populations especially in evacuation centers.…”
Section: Articles Related With Geje In Tjem After 2011mentioning
confidence: 99%
“…Females are twice as likely to suffer from sleep disruptions as males (Mong et al, 2011 ). During a previous earthquake crisis, sleep disturbances were more prevalent among females than males (Nakamura et al, 2020 ). In addition, gender differences have been reported in the experience of mental health issues.…”
Section: Introductionmentioning
confidence: 99%